Color Doppler Evaluation of Cerebral - Umbilical Pulsatility Ratio and its Usefulness in the Diagnosis of Intrauterine Growth Retardation and Prediction of Adverse Perinatal Outcome - Mahmood, Sharmeen; Chowdhury, Shiuly; Chowdhury, Saleha Begum (Journal of Bangladesh College of Physicians and Surgeons, 2017)
The purpose of this study is Evaluation of cerebral umbilical pulsatility ratio by color Doppler and to estimate the value of pulsatility index ratio of cerebral umbilical vessels in the diagnosis of small-for-gestational-age (SGA) fetuses and in the prediction of adverse perinatal outcome . Validity of the test were confirmed by determining sensitivity, specificity, accuracy, positive predictive value, negative predictive value. The study population comprised 40 pregnancies of 30-41 weeks gestation that had been diagnosed clinically as intrauterine growth retardation (IUGR) over a period of 1 year. The cerebral - umbilical pulsatility ratio (C/U ratio) were calculated. The pregnancies were followed up and the final perinatal outcome of each case were noted. Various intraparum and neonatal indicators were used to assess the outcome, with an adverse outcome being defined as the presence of one or more of these indicators. The most common adverse perinatal outcome was birth asphyxia, low apgar score, stay at NICU, still birth and caesarean section for fetal distress. Of the 40 pregnancies in the study, 30 (75%) showed abnormal C/U ratio. Among these, 32 (80%) were SGA and 32 (80%) had adverse perinatal outcome. Of the 30 out of 40 pregnancies that showed abnormal C/U ratio (<1.08), all 30 (80%) were SGA and had adverse perinatal outcome. The results were correlated with parameters of fetal outcome. Inferences drawn from the study was that C/U ratio is a tools for prediction of SGA fetuses and adverse perinatal outcome. J Bangladesh Coll Phys Surg 2016; 34(3): 145-150